Comparison of standard methods for evaluating the metal concentrations in bio ash. (2017) - Pesonen, Janne; Kaakinen, Juhani; Valimaki, Ilkka; Illikainen, Mirja; Kuokkanen, Toivo
The current growth strategy and environmental legislation of the European Union both aim to increase the amount of renewable energy and to improve the use of waste streams. These policies mean there will be an increasing need to utilise bio ash. Currently, Finland and Denmark are the only European countries with specific national legislation concerning bio ash use. Sweden has recommendations concerning the use of bio ash fertilisers. Besides having different limit values for harmful elements and nutrients in ash fertilisers, all these countries have different digestion methods that are allowed for element content determinations. This study compared the results of the five digestion methods (aqua regia, nitric acid, nitric/hydrochloric acids, nitric/hydrochloric/hydrogen fluoride acids, and lithium tetraborate fusion) established by Nordic authorities. Two Finnish peat-wood fly ash samples were studied. Our results indicate that the choice of digestion methods produces a significant difference in the obtained heavy metal or nutrient concentration of bio ash, especially regarding the potassium concentration.